Skin cancer in solid organ transplant recipients: still an open problem - Granata, Simona; Tessari, Gianpaolo; Stallone, Giovanni; Zaza, Gianluigi (Frontiers in Medicine, 2023)
In the last two decades, the optimization of organ preservation and surgical techniques, and the personalized immunosuppression have reduced the rate of acute rejections and early post-transplant complications. However, long-term graft survival rates have not improved over time, and evidence suggest a role of chronic calcineurin inhibitor toxicity in this failure. Solid organ transplant recipients may develop chronic dysfunction/damage and several comorbidities, including post-transplant malignancies. Skin cancers, mostly non-melanoma skin cancers (squamous cell carcinoma and basal cell carcinoma), are the most common malignancies in Caucasian solid organ transplant recipients. Several factors, together with immunosuppression, may contribute to the susceptibility for skin cancers which, although often treatable, could be associated with a much higher mortality rate than in the general population. The rapid identification and treatment (including reduction of immunosuppression and early surgical treatments) have an important role to avoid an aggressive behavior of these malignancies. Organ transplant recipients with a history of skin cancer should be followed closely for developing new and metastatic lesions. Additionally, patient education on the daily use of sun-protective measures and the recognition of the early signs (self-diagnosis) of coetaneous malignancies are useful preventive measures. Finally, clinicians should make themselves aware of the problem and build, in every clinical follow-up center, collaborative network involving transplant clinicians, dermatologists and surgeons who should work together to easily identify and rapidly treat these complications. In this review, we discuss the current literature regarding the epidemiology, risk factors, diagnosis, preventive strategies and treatments of skin cancer in organ transplantation.